(untitled) (Medicine Today, 2014)
Neonatal sepsis is a major cause of mortality and morbidity in newborn, particularly in developing countries. The spectrum of bacteria which causes neonatal sepsis varies in different parts of the world. The organisms responsible for early onset and late onset sepsis are different. The objective of the study was undertaken to determine the pattern of bacterial isolates responsible for early and late onset neonatal sepsis based on the presence of one or more clinical signs, and its outcome. A cross- sectional prospective study was carried out in the special care baby unit (SCABU) from November 2008 to September 2009 under department of Paediatrics and Neonatology, BIRDEM General Hospital, Dhaka, Bangladesh. Organisms were isolated from 8.9% of collected blood samples. The male female ratio of culture proven sepsis was 1.7:1. Most of the culture proven septic neonates(71.88%) were preterm & 65.63% had low birth weight. The most frequent clinical presentations of patients with culture-proven sepsis were poor moro reflex (92.2%), feeding intolerance (90.6%), jaundice (87.5%), abdominal distention (76.6%), and lathergy (73.4%). The Gram positive and Gram negative bacteria accounted for 6 (9.4% ) and 58 (90.6%) of the isolates respectively. Around two third of the culture-proven septic neonates (70.3%) presented with early onset sepsis, while 29.7% presented with late onset sepsis. Klebsiella pneumoniae was the most common pathogen both in early onset (31.25%) and late onset (6.25%) sepsis. Serratia (18.75%) was the second most common pathogen in early onset sepsis. Total mortality rate was 9.38%. Preterm, low birth weight and Gram negative sepsis contributes majority of mortality. Gram negative organism especially Klebsiella pneumoniae contributed highest in early onset sepsis and neonatal death (6.25%) due to sepsis. DOI: http://dx.doi.org/10.3329/medtoday.v26i1.21306 Medicine Today 2014 Vol.26(1): 18-21